Improved Results Over Time With Bridge-to-Lung Transplantation: A 10-Year Experience of a Single High-Volume Center - Gyungah Kim; Jee Hwan Ahn; Tae Sun Shim; Pil-Je Kang; Geun Dong Lee; Sehoon Choi; Won Kim; Sung-Ho Jung; Dong Kwan Kim; Seung-Il Park; Sang-Bum Hong (Transplant International)
When donor scarcity limits timely lung transplantation (LTx), extracorporeal membrane oxygenation (ECMO) as a bridge to transplantation (BTT) can prolong survival and delay deconditioning until the donor lungs become available. We reviewed 10-year BTT experiences of a single high-volume center, where 99 (59%) were on ECMO BTT among 169 eligible adult LTx cases. Both 28-day and 2-year survivals did not differ between BTT and non-BTT. The BTT data was then divided into two periods, delineated by the most recent 3 years. The clinical outcomes of the earlier period (“Period 1”) and the later period (“Period 2”) were compared, and mortality within 28 days of LTx was significantly lower in Period 2 (n = 1, 1.7%) than in Period 1 (n = 6, 14.6%, p < 0.01). Improved survival was observed in the subgroup with BTT duration of 14 days or more. Taken together, more experiences in BTT and improved competence may contribute to better survival after LTx, especially in patients receiving ECMO for 14 days or more.